Script and society: the social context of writing practices in late Bronze Age Ugarit - Boyes, Philip J. (Contexts of and Relations between Early Writing Systems, 2021)
By the 13th century BC, the Syrian city of Ugarit hosted an extremely diverse range of writing practices. As well as two main scripts - alphabetic and logographic cuneiform - the site has also produced inscriptions in a wide range of scripts and languages, including Hurrian, Sumerian, Hittite, Egyptian hieroglyphs, Luwian hieroglyphs and Cypro-Minoan. This variety in script and language is accompanied by writing practices that blend influences from Mesopotamian, Anatolian and Levantine traditions together with what seem to be distinctive local innovations. Script and Society: The Social Context of Writing Practices in Late Bronze Age Ugarit explores the social and cultural context of these complex writing traditions from the perspective of writing as a social practice. It combines archaeology, epigraphy, history and anthropology to present a highly interdisciplinary exploration of social questions relating to writing at the site, including matters of gender, ethnicity, status and other forms of identity, the relationship between writing and place, and the complex relationships between inscribed and uninscribed objects. This forms a case- study for a wider discussion of interdisciplinary approaches to the study of writing practices in the ancient world